Diazonium Salts as Nitrogen-Based Lewis Acids - Habraken, Evi R. M.; Jupp, Andrew R.; Slootweg, J. Chris (Synlett, 2019)
Aryldiazonium salts are widely used in many organic transformations with displacement of N2 or through addition to the terminal nitrogen. Such aryldiazonium salts can be viewed as N-based Lewis acids that can react with Lewis bases to synthesize a wide variety of azo compounds. Additionally, diazonium salts are known to undergo single-electron transfer and release N2, forming an aryl radical, which results in different reactivity. Herein, we provide a concise overview of the reactivity of aryldiazonium salts undergoing classical donor-acceptor reactivity or single-electron transfer.
Keywords: diazonium salts; donor–acceptor adducts; N-based Lewis acids; phosphines; carbenes; radicals